Documenting Wixárika Oral Knowledge with Young People Using Traditional and Digital Technologies in Art Workshops - Kantonen, Lea; Kantonen, Pekka (Palgrave Macmillan, 2025)
The Wixárika people (plur. Wixaritaari) living in Western Mexico foster an ancestral oral knowledge of ritual art and crafts, stories, and long epic songs. It is traditionally documented by craft-based technologies, today increasingly digital technologies. The data of this case study on Wixárika art education is achieved using artistic action research methods. It is based on our experience as facilitators of art workshops with young Wixaritaari, and our interviews with two Wixárika authorities: Neikame Julio Ramirez Carrillo, PhD, linguist and educator, and ‘Uutɨama Apolonia de la Cruz Ramirez, traditional authority and teacher of textile crafts and Wixárika grammar, as well as on earlier discussions and data collected with teachers and students at Tatuutsi Maxakwaxi School. We demonstrate that many young Wixaritaari master both craft-based and digital technologies to express ancestral knowledge and map their sacred places and cardinal directions. In Neikame's view, technology as such neither promotes nor repudiates the traditional lifestyle of the Wixárika, the yeiyari, the path of the ancestors, but it is a matter of how much adults care about and guide young people. It is up to adults to teach young people, take them to ceremonies, speak Wixárika to them, and filter useful information from the web to help them understand the world better.
Keywords: taide; käsityö (toiminta); alkuperäiskansat; taiteellinen tutkimus; suullinen perinne; teknologia